Transformational Leadership in Remote Schools: Integrating Local Cultural Values and Stakeholder Collaboration for Educational Improvement - Arismin; Ismail; Niswanto; Safii (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
The transformation of school leadership in remote areas plays a strategic role in overcoming limitations in access, resources, and educational facilities. As an archipelago with geographic isolation, the country faces significant challenges that affect the quality of learning and teacher professionalism. This study aims to analyze the implementation of transformational leadership through the formulation of contextual vision and mission, strengthening teacher motivation and commitment, and building collaboration with stakeholders. Using a qualitative descriptive method with a case study design, data were collected through in-depth interviews, participant observation, and document analysis, and then analyzed thematically. The findings show that school principals formulated adaptive, realistic, and inspiring visions by integrating local potential and coping strategies to address limitations. Teacher motivation and commitment increased through empowerment, positive reinforcement, emotional support, and role modeling. Furthermore, collaboration with the community, government, and external stakeholders strengthened legitimacy and resource availability. These findings confirm that transformational leadership is both practical and effective in improving educational quality in remote areas. The study also highlights the importance of context-sensitive leadership in addressing the unique challenges schools face in these areas. Therefore, this research recommends leadership training grounded in local wisdom for school principals, increased facility support and incentives from local governments, and strengthened collaboration among schools, communities, and stakeholders to maximize the utilization of available resources.